Tan Star HR Management System - Visvanathan, Yubaasini; Nurul Aswa Omar, (Applied Information Technology And Computer Science, 2024)
The Tan Star HR Management System (TS-HRMS) is a web-based system designed to revolutionize human data management in organizations. The system aims to address issues such as time-consuming data retrieval, errors, and potential employee misidentification. The system includes features like transparent access to salary history, streamlined profile maintenance, quick processing of leave requests, and user- friendly dashboards. The project uses advanced technology which is Hypertext Preprocessor (PHP) for programming language and XAMPP Control Panel for database where by using a methodical approach with waterfall design phases and rigorous testing to ensure a reliable and error-free system. TS-HRMS accommodates the unique needs of various organizations through scalability and customization, promoting improved operational agility and organizational performance. The project is expected to change HR management, bringing about a new era of accessible, accurate, and efficient personnel data management.